Assessing statistical reasoning, attitude towards statistics, and statistics anxiety among rural secondary students in the Northern West Coast of Sabah - Siti Shahirah Saidi (2020)
Assessing students‘ statistical reasoning becomes one of the focuses of interest in statistics educational research, in addition to assessing the non-cognitive factors that can influence students‘ learning in statistics. Many students are likely to have trouble with statistics due to non-cognitive factors, such as attitudes and anxiety towards statistics. A survey research was conducted on the Form 4 science stream students who studied in the rural secondary schools in the Northern West Coast of Sabah in order to assess their statistical reasoning, attitude towards statistics, and statistics anxiety. A total of 320 students were sampled in this study by using two types of sampling. The sample was stratified first based on the District Education Office (PPD) using the stratified sampling technique, and then half numbers of schools in each of PPD were selected randomly by using the probability proportional to size sampling technique. A Statistical Reasoning Test Survey (SRTS), Survey Attitude towards Statistics (SATS), and Statistical Anxiety Scale (SAS) were administered to the students in order to assess students‘ statistical reasoning, attitude towards statistics, and statistics anxiety respectively. The data obtained were analyzed descriptively and inferentially by using IBM SPSS version 20.0 and IBM AMOS version 22.0. Based on the findings, it was revealed that the students had a quite high level (Quantitative level/ Level 3) in statistical reasoning, a positive attitude towards statistics, and a moderate level of statistics anxiety. Besides that, a significant gender difference was found in the Effort component in SATS and in the Examination Anxiety and Interpretation Anxiety components in SAS. Furthermore, a significant positive relationship was observed between the attitude towards statistics and statistical reasoning, between attitude towards statistics with the Organizing Data and Representing Data construct, and between Cognitive Competence, and Value component with the statistical reasoning. Meanwhile, a significant negative relationship was observed between the statistics anxiety and statistical reasoning, between students‘ statistics anxiety with the Describing Data, Organizing Data, and Representing Data construct, and between Asking for Help Anxiety and Interpretation Anxiety component with statistical reasoning. Other than that, in the assessment of the influence of attitude towards statistics and statistics anxiety components on students‘ statistical reasoning, this study found that only Value, Interest, and Interpretation Anxiety components had significant influence on students‘ statistical reasoning which explained about 10.3% variance in students‘ statistical reasoning. The structural model that was proposed in this study was suitable with the data of the study since the assessment through the Goodness of Fit Indices showed that all of the fit indices value assessing the model fit was in the acceptable range. Overall, the findings of this study are expected to assist mathematics educators to develop better lesson plans and identify instructional techniques which could improve students‘ statistical reasoning, increase attitude towards statistics, and reduce statistics anxiety. For these purposes, mathematics educators may implement the Statistical Reasoning Learning Environment (SRLE) in the classroom and use humor in teaching.